Lena Smart Pillow / Nur Hafizah Ali, Ahmad Mustaqim Naim Abdul Ghafar … [et al.] - Ali, Nur Hafizah; Abdul Ghafar, Ahmad Mustaqim Naim; Abdul Zaman, Muhammad Aminuddin Sz; Mat Ahan, Mohd Fadzil (2019)
Mawaddah Group Sdn. Bhd. have new product to be introduce to the consumers which is the smart pillow or known as 'Lena Smart Pillow'. Our company targeting in providing a smart pillow since it is every person for all range of old especially for people that working or still studying needs to have enough rest and sleeping time and pillow that have lots of featuring that can help in daily live. Our smart pillow is user-friendly, eco friendly and easy to use. Normally, normal pillow in market only provide people with basic need for placing their head even the pillow sometime not have ergonomic feature for our neck. Therefore, 'Lena Smart Pillow' can help the users to have one pillow that have all feature that normal pillow lack..